TRANSFORMATION OF PANCASILA EDUCATION BASED ON SASAMBO LOCAL WISDOM FOR THE DEVELOPMENT OF STUDENTS' SOCIAL CHARACTER IN THE DIGITAL ERA - Ardiansyah, Suriadi; Satria Mandala, Opan (The Indonesian Journal of Social Studies, 2025)
This study analyzes the transformation of Pancasila Education through the integration of SASAMBO local wisdom values (Sasak, Samawa, and Mbojo) in the formation of students' social character in the digital era. The novelty of this research lies in the development of a conceptual framework that connects SASAMBO's local values with digital-based social character competencies, which have not been elaborated much in the study of Pancasila Education. Using a qualitative approach with the literature study method, the analysis was carried out through thematic content analysis which included the process of identifying, categorization, and interpreting the main themes based on 41 selected scientific sources, including national-international journals, academic books, and education policy documents. Validation of findings is carried out through source triangulation to ensure data consistency and reliability. The results of the study show that the values of begawe (mutual cooperation), saleng pedi (empathy), and maja labo dahu (integrity) contribute significantly in strengthening the social character of students in the context of digital interaction. The integration of these values through project-based learning models and digital media results in more adaptive and contextual character strengthening patterns. Theoretically, this research enriches the perspective of Pancasila Education based on local wisdom; Practically, it offers a relevant implementation model to shape the social character of students in the digital era.